Genetics and Gene Manipulation. - Martin, Marjory-Dore; Gleeson, Dawn; Kinnear, Judith ([Deakin University], 1996)
Final report of a project at Deakin University, School of Scientific and Development Studies. The aim of the project was to produce a CD-ROM package that would have a significant positive impact on student learning and enhance the teaching of genetics. The CD-ROM program developed was designed for use in introductory genetics programs at the undergraduate tertiary education level. It comprises three modules: Chromosomes, Genes and Alleles, and DNA - The Genetic Material. The program was designed to facilitate and enhance learning in users through clear presentation, opportunities for user control, randomly generated activities, multiple pathways, self-tests and feedback and a glossary. An accompanying booklet contains test sheets of selected topics.